PENGARUH KEBIJAKAN DIVIDEN TERHADAP KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN (STUDY PADA MANUFACTURING COMPANIES YANG TERCATAT DI BURSA EFEK INDONESIA) - Nuzil, Nur Rohmad (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2017)
This study aims to determine whether there is influence devidend policy on corporate performance and corporate value, where the value of the company is very important, especially in the company go public because of the high value of the company to be followed. by the shareholders of high prosperity. The purpose of this research is to know the effect of dividend policy (as measured by DPR) on company performance (as measured by ROA and ROE) and value of company (as measured by Tobin's q), Population in this research is manufacturing company listed on Bursa Effects from 2010 to 2014. Methods of sampling in this study by using non-random sampling method. The sample in this research is 10 manufacturing companies. Research data was obtained from www.idx.co.id. And ICMD 2010-2014. Testing this hypothesis using path analysis model research and data processing using SPSS (Statistical product and service solutions). Result of research: 1) dividend policy influence negative and no significant effect to company performance, 2) dividend policy have positive effect and no significant effect to company, and 3) company performance have significant positive impact to company value. Thus, the hypothesis proposed in this study has been tested. It is recommended in subsequent research to develop other variables in this study.